Where has all the dynamism gone? Productivity growth in China's manufacturing sector, 1998-2013 - Loren Brandt; Johannes Van Biesebroeck; Luhang Wang; Yifan Zhang (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
China's manufacturing sector has been a key source of the economy's dynamism. Analysis after 2007 however is hampered by problems in the key data source for empirical analysis, the National Bureau of Statistics' (NBS) annual survey of industrial firms. Issues include missing information on value added and intermediate inputs, and concerns of over-reporting. The annual survey of firms conducted by China's State Taxation Administration (STA) provides a reliable, alternative source of firm-level data for years from 2007 to 2013. Since the sample is not representative and the precise sampling scheme is not known, the data cannot be used directly to draw inferences on China's manufacturing sector. By comparing the joint distribution of key variables for which both surveys provide reasonably reliable information, we recover the sampling scheme of the STA survey and use it to simulate samples for 2007 to 2013 that are comparable to the NBS sample in earlier years. Our estimates reveal a marked slowdown in revenue-based total factor productivity growth that cuts across all industries, ownership types, and regions. The loss of dynamism in the private sector, and the reduced contribution of firm entry to aggregate productivity growth are especially prominent.
urn:nbn:fi-fe20231130150500
Keywords: D24; O14; 330; TFP; Industrial development; Economic growth